Produção de celulases por Myceliophthora thermophila I-1D3b em resposta a diferentes fontes de carbono e taxas de aeração em cultivos sólido e submerso - Mafra, Nilton Silva Costa (2023)
The interest in cellulolytic systems of thermophilic fungi motivated the development of research aimed at the use of their enzymes in various industrial sectors, such as in the production of biofuels, particularly second-generation bioethanol (BE2G). The fungus Myceliophthora thermophila I-1D3b has proved to be an excellent producer of cellulases; however, there is little knowledge about its metabolism. Thus, the objective of this work was to experimentally analyze the effect of different carbon sources and aeration rates on the ability to activate or inhibit cellulase production by the fungus Myceliophthora thermophila I-1D3b in solid state (CES) and submerged (CSm) cultivations. Glucose, sucrose, fructose and lactose were evaluated as carbon sources at concentrations 5, 10 and 15 g.L-1, as for aeration rates 0.5 and 1 vvm were tested. The tests for the cultivations in solid and submerged medium were conducted at 45ºC for 96 h. Initially, on flasks scale, it has been evaluated the influence of carbon sources on the induction of enzymatic production and the addition of lactose and other compounds likely inducers to the inoculum preparation medium, as well as the effect of the proportion sugarcane bagasse and wheat bran on substrate composition. The replacement of synthetic lactose medium by fresh whey was also evaluated. In the tests on packed bed bioreactor for CES and aerated stirred tank for CSm, the effects of variation in aeration rate on growth and secretion of enzymes were studied. Flasks-scale cultivations showed that lactose was considered a promising inducer for endoglucanase synthesis at the concentration of 15 g.L-1, achieving activities of 210 and 120 U.gss-1 in solid and submerged cultivations, respectively, for mass proportion 7:3 of sugarcane bagasse and wheat bran. The addition of lactose to the inoculum preparation medium was not interesting, not increasing significantly endoglucanase activities. The assays with fresh whey showed results close to the control performed with the use of synthetic lactose, which shows their perspective of reuse. The analyses in bioreactors showed that time-profiles of temperature and CO2 concentration did not present significant variation (95% confidence) with the increase of the aeration rate. Nevertheless, in the operation with 1 vvm, a higher volume of CO2 released was observed, which reflected in higher enzymatic production. Thus, the operation with 1 vvm proved to be applicable and advantageous to produce cellulase.